PENGARUH TEKNOLOGI DAN TUNTUTAN KONSUMEN TERHADAP PROFESI AKUNTANSI SAAT INI - Abdullah Taman (Jurnal Pendidikan Akuntansi Indonesia, 2004)
PENGARUH TEKNOLOGI DAN TUNTUTAN KONSUMEN TERHADAP PROFESI AKUNTANSI SAAT INIThe objective of this article is to describe how technology and customer need influence accounting profession. Advanced technology has been changing almost all of human life. Innovations of computer equipment and program, as well as manufacturing tools influence accounting profession. This can be shown by generating various kinds of accounting computer application program and application of Material Requirement Planning (MRP), Computer Integrated Manufacturing (CIM), and Statistical Process Control (SPC). Customer’s need of accounting profession also has been changing paradigm that is as long as adhered. Conventional accounting is connoted by bookkeeping and auditing, while recently it is forced to develop its knowledge content and extent service spectrum e.g. management consultancy, strategic planning, and service consultancy of ISO 9000 and 14000.   Keywords: accounting, influence, profession, technology